Equilibria in some families of Kolmogorov systems. (April 2017) - Bravo, José Luis; Fernández, Manuel; Tineo, Antonio
Abstract: Kolmogorov systems constitute a general model for the dynamics of biological species. In that sense, they are generalizations of the Lotka–Volterra systems. Here, some classical results on existence, uniqueness, and global attraction of local equilibria that hold in Lotka–Volterra systems are generalized to Kolmogorov systems.